Quantifying rooting at depth in a wheat doubled haploid population with introgression from wild emmer - Clarke, Christina K; Gregory, Peter J; Lukac, Martin; Burridge, Amanda J; Allen, Alexandra M; Edwards, Keith J; Gooding, Mike J (Annals of botany, 2017)
BACKGROUND AND AIMS: The genetic basis of increased rooting below the plough layer, post-anthesis in the field, of an elite wheat line (Triticum aestivum 'Shamrock') with recent introgression from wild emmer (T. dicoccoides), is investigated. Shamrock has a non-glaucous canopy phenotype mapped to the short arm of chromosome 2B (2BS), derived from the wild emmer. A secondary aim was to determine whether genetic effects found in the field could have been predicted by other assessment methods. METHODS: Roots of doubled haploid (DH) lines from a winter wheat ('Shamrock' × 'Shango') population were assessed using a seedling screen in moist paper rolls, in rhizotrons to the end of tillering, and in the field post-anthesis. A linkage map was produced using single nucleotide polymorphism markers to identify quantitative trait loci (QTLs) for rooting traits. KEY RESULTS: Shamrock had greater root length density (RLD) at depth than Shango, in the field and within the rhizotrons. The DH population exhibited diversity for rooting traits within the three environments studied. QTLs were identified on chromosomes 5D, 6B and 7B, explaining variation in RLD post-anthesis in the field. Effects associated with the non-glaucous trait on RLD interacted significantly with depth in the field, and some of this interaction mapped to 2BS. The effect of genotype was strongly influenced by the method of root assessment, e.g. glaucousness expressed in the field was negatively associated with root length in the rhizotrons, but positively associated with length in the seedling screen. CONCLUSIONS: To our knowledge, this is the first study to identify QTLs for rooting at depth in field-grown wheat at mature growth stages. Within the population studied here, our results are consistent with the hypothesis that some of the variation in rooting is associated with recent introgression from wild emmer. The expression of genetic effects differed between the methods of root assessment.
Keywords: haploidie; Triticum; Genotype; Phenotype; mapování chromozomů; Chromosome Mapping; Triticum aestivum (wheat); genotyp; doubled haploid; drought; phenotyping; Plant Roots; root length density; Deep rooting; Triticum dicoccoides (wild emmer); Quantitative Trait Loci; fenotyp; lokus kvantitativního znaku; pšenice; Haploidy; rhizotron; kořeny rostlin; seedling screen